Mutation of MEF2A in an Inherited Disorder with Features of Coronary Artery Disease - Wang, Lejin (2003)
The early genetic pathway(s) triggering the pathogenesis of coronary artery disease (CAD) and myocardial infarction (MI) remain largely unknown. Here, we describe an autosomal dominant form of CAD/MI (adCAD1) that is caused by the deletion of seven amino acids in transcription factor MEF2A. The deletion disrupts nuclear localization of MEF2A, reduces MEF2A-mediated transcription activation, and abolishes synergistic activation by MEF2A and by the transcription factor GATA-1 through a dominant-negative mechanism. The MEF2A protein demonstrates strong expression in the endothelium of coronary arteries. These results identify a pathogenic gene for a familial vascular disease with features of CAD and implicate the MEF2A signaling pathway in the pathogenesis of CAD/MI.